Pemanfaatan Media Belajar Ikan Mujair Pada Mata Pelajaran IPA Materi Organ Pernapasan pada Hewan Untuk Sekolah Dasar - Zubaidah, Indah (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
The use of mujair fish learning media by teachers in the implementation of science learning activities in class V MI Ma'arif NU 2 Sanggreman, Rawalo District, Banyumas District, the results show the direction of increasing learning activities both in terms of activities and learning outcomes. The results of the implementation of science learning activities breathing material material on animals by utilizing tilapia fish learning media showed maximum results. The number of KKM students is 17 (89%) students and not yet KKM is only 2 (11%) students. And classical has reached classical completeness, namely the number of students who reach KKM is 84.21.